2004
DOI: 10.1097/00007632-200405150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Facet Angles in Lumbar Disc Herniation: Their Relation to Anthropometric Features

Abstract: This study revealed that patients with lumbar disc herniation had the asymmetry and sagittalization of facet joints, and these alterations were more evident in the taller patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
91
1
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 13 publications
5
91
1
9
Order By: Relevance
“…The larger synovial fold volume was associated with taller subjects and with those who weighed less and had a lower BMI. This is in contrast to the dimensions of the articular facets, spinal cord and some cervical muscles, which typically increase in size in association with greater body size [10,31,41,61]. Although, in the main, synovial fold volume was not as strongly related to the dimensions of the head and neck, there was a general trend for synovial fold volume to increase with increasing neck length and to increase with decreasing head and neck circumference, i.e.…”
Section: Discussionmentioning
confidence: 73%
“…The larger synovial fold volume was associated with taller subjects and with those who weighed less and had a lower BMI. This is in contrast to the dimensions of the articular facets, spinal cord and some cervical muscles, which typically increase in size in association with greater body size [10,31,41,61]. Although, in the main, synovial fold volume was not as strongly related to the dimensions of the head and neck, there was a general trend for synovial fold volume to increase with increasing neck length and to increase with decreasing head and neck circumference, i.e.…”
Section: Discussionmentioning
confidence: 73%
“…Kunakornsawat et al 19 defined FT as a 5° differential between left and right facet joint angle in the same segment, and they found no exact association between FT and LDH. Karacan et al 14 defined FT as the bilateral angle difference greater than 2 intraobserver errors, and they found that FT was more prominent in the LDH group. Kong et al 17 defined FT as a 7° difference between bilateral facet joints in the same segment, and no significant correlation was observed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…There is controversy concerning the relationship between facet joint asymmetry and lumbar spinal degeneration [4][5][6][7][8][9][10][11][12][13][14][15][16]. Karacan and colleagues [5] stated that asymmetry of the facet joints strongly correlates with the development of lumbar disc herniation. Moreover, facet joint asymmetry might be a risk factor for the development of lumbar disc degeneration [7], or lumbar spondylolisthesis [4,6].…”
Section: Discussionmentioning
confidence: 99%